Effects of Liraglutide on Weight Loss, Fat Distribution, and β-Cell Function in Obese Subjects With Prediabetes or Early Type 2 Diabetes - Santilli, Francesca; Simeone, Paola G.; Guagnano, Maria T.; Leo, Marika; Maccarone, Marica T.; Di Castelnuovo, Augusto; Sborgia, Cristina; Bonadonna, Riccardo C.; Angelucci, Ermanno; Federico, Virginia; Cianfarani, Stefano; Manzoli, Lamberto; et al. (Diabetes care, 2017)
Obesity is associated with an increased risk of type 2 diabetes and cardiovascular complications. The risk depends significantly on adipose tissue distribution. Liraglutide, a glucagon-like peptide 1 analog, is associated with weight loss, improved glycemic control, and reduced cardiovascular risk. We determined whether an equal degree of weight loss by liraglutide or lifestyle changes has a different impact on subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) in obese subjects with prediabetes or early type 2 diabetes. Sixty-two metformin-treated obese subjects with prediabetes or newly diagnosed type 2 diabetes, were randomized to liraglutide (1.8 mg/day) or lifestyle counseling. Changes in SAT and VAT levels (determined by abdominal MRI), insulin sensitivity (according to the Matsuda index), and β-cell function (β-index) were assessed during a multiple-sampling oral glucose tolerance test; and circulating levels of IGF-I and IGF-II were assessed before and after a comparable weight loss (7% of initial body weight). After comparable weight loss, achieved by 20 patients per arm, and superimposable glycemic control, as reflected by HbA level ( = 0.60), reduction in VAT was significantly higher in the liraglutide arm than in the lifestyle arm ( = 0.028), in parallel with a greater improvement in β-index ( = 0.021). No differences were observed in SAT reduction ( = 0.64). IGF-II serum levels were significantly increased ( = 0.024) only with liraglutide administration, and the increase in IGF-II levels correlated with both a decrease in VAT (ρ = -0.435, = 0.056) and an increase in the β-index (ρ = 0.55, = 0.012). Liraglutide effects on visceral obesity and β-cell function might provide a rationale for using this molecule in obese subjects in an early phase of glucose metabolism dysregulation natural history.